Fusarium solani causing quasi-invasive infection of the foot in an immunocompetent middle-aged man from South India - Mohan H Kudur; P Y Prakash; M Savitha (Wolters Kluwer Medknow Publications, 2013)
Fusarium solani is commonly found in soil, and it is associated with infections in immunocompromised individuals. Fusaroium solani causing infection in immunocompetent adult male is rare and usually overlooked. We report a case of mycetoma caused by Fusariom solani in an immunocompetent adult male from South India.